The Fight for Substantive Equality: Women's Activism and Section 15 of the Canadian Charter of Rights and Freedoms - Eberts, Mary (Atlantis)

(untitled) (Mount Saint Vincent University, 2015)
This article discusses the role of women’s groups in the development of section 15 of the Canadian Charter of Rights and Freedoms, the Charter’s principal equality rights guarantee, entrenched in the Constitution in 1981. Thanks to the leadership of Doris Anderson, submissions to the Special Joint Committee on the Constitution from the Canadian Advisory Council on the Status of Women (CACSW), the National Action Committee on the Status of Women (NAC), and the National Association of Women and the Law (NAWL) were instrumental in securing changes to section 15. However, the version in the entrenched Charter still fell short of women’s aspirations.